Pemberdayaan Tanah Wakaf Sebagai Media Ketahanan Pangan Berbasis Kearifan Lokal Di Desa Kadumekar - Jalaludin, Jalaludin; Alamdhien, Hadi; Maulana, Deni; Ihsan, Ahmad Maulana (STIE Syariah Indonesia Purwakarta, 2025)
Based on the results of observations, the PKM team found several unique phenomena related to the empowerment of waqf land as a medium for local wisdom-based food security in Kadumekar Village, one of which is that public cemetery waqf land is still rarely used for the benefit of the community, the knowledge and behavior of the community who still blame each other regarding the use of waqf land, the harvest from the use of waqf land is used for the benefit of the community and the operation of the waqf manager. The purpose of this PKM is to carry out the empowerment of waqf land as a medium for local wisdom-based food security in Kadumekar Village. This PKM method uses observation, socialization and mentoring, monitoring and evaluation. The conclusion in this PKM is that the level of understanding of PKM partners before the implementation of mentoring activities gets a minimum score of 10/100 and the highest gets a score of 60/100, but after the implementation of mentoring activities gets a minimum score of 60/100, and a maximum score of 100/100. When averaged, the level of understanding of PKM partners has changed from an average score of 25.5 points in the category of very not understanding, changing drastically to 87 points in the category of very understanding. This achievement according to the PKM team is a very significant achievement. In addition, this PKM has a positive impact on the community in the form of understanding the definition of waqf land in detail, food security, the benefits of waqf land, utilization of waqf land based on local wisdom, challenges in utilizing waqf land, opportunities for diversification of waqf land management, waqf land management models, challenges in empowerment and knowing the positive impact of waqf land empowerment.